2009
DOI: 10.1016/j.joca.2008.05.021
|View full text |Cite
|
Sign up to set email alerts
|

Altered functional loading causes differential effects in the subchondral bone and condylar cartilage in the temporomandibular joint from young mice

Abstract: Summary Objective Altered loading is an important etiological factor for temporomandibular joint (TMJ) disorders. Studies examining altered loading of the TMJ have been done in rats but the response of the TMJ to altered loading in mice is largely unknown. Therefore, due to the potential usefulness of genetically engineered mice, the goal of this study was to develop a mouse TMJ altered functional loading model. Methods One hundred and thirty four, 21-day-old CD-1 female mice were divided into two groups: (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
73
2
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 93 publications
(93 citation statements)
references
References 22 publications
11
73
2
2
Order By: Relevance
“…When muscle loading was removed at birth, there was an increase in the number of Hh-responsive cells at P28. This result complements previous studies that have shown that Ihh expression is either upregulated or downregulated in response to increased or decreased cyclic compressive loading, respectively (Chen et al, 2009;Ng et al, 2006;Shao et al, 2012;Wu et al, 2001). In the current study, decreased cyclic tensile loads led to increased Ihh signaling.…”
Section: Discussionsupporting
confidence: 91%
“…When muscle loading was removed at birth, there was an increase in the number of Hh-responsive cells at P28. This result complements previous studies that have shown that Ihh expression is either upregulated or downregulated in response to increased or decreased cyclic compressive loading, respectively (Chen et al, 2009;Ng et al, 2006;Shao et al, 2012;Wu et al, 2001). In the current study, decreased cyclic tensile loads led to increased Ihh signaling.…”
Section: Discussionsupporting
confidence: 91%
“…It has also been suggested that the cartilage of TMJ in normal mice is replaced by fibrocartilage, and is histologically established at 30 weeks of age (19). The articular cartilage of the condyle in STR/ort mice appears to develop spontaneous OA-like lesions that resemble human OA; therefore, the STR/ort mouse strain would be a useful model to study the pathogenesis of TMJ OA.…”
Section: Discussionmentioning
confidence: 99%
“…Reactivation of chondrogenesis is seen whenever remodeling is stimulated by alterations in biomechanical forces [Lindsay, 1977;Bouvier, 1988;Rashed and Sharawy, 1993;Mao et al, 1998;Chaves et al, 2002;Huang et al, 2002;Rabie et al, 2003;Shen and Darendeliler, 2005;Chu, 2008]. Changes in the thickness of the layers are observed during remodeling of the condylar cartilage [Bouvier, 1988;Bibb et al, 1992;Paulsen et al, 1999;Visnapuu et al, 2000;Rabie et al, 2003;Wang and Detamore, 2007;Chen et al, 2009]; thickening of the proliferative layer is a marker of bone growth [Bouvier, 1988;Bibb et al, 1992]. Many experimental works in the literature examining the morphology of mandibular condylar cartilage after alterations induced by the presence of an occlusal interference [Rashed and Sharawy, 1993;Chaves et al, 2002] or secondary to articular disc displacements [Ali et al, 1993;Ali and Sharawy, 1994, 1995, 1996Narinobou et al, 2000;Sharawy et al, 2003] employ rabbits as the experimental model, more specifically the New Zealand type (Oryctolagus cunniculus) as its TMJ most closely resembles the human TMJ functionally [Weijs and Dantuma, 1981;Tallents et al, 1990;Dan'kov, 1993;Herring, 2003].…”
Section: Introductionmentioning
confidence: 99%